(untitled) (Third Sector Social Economic Review, 2022)
In today’s world, both individual and corporate economic literacy are seen among basic knowledge and skills. Evaluating economic conditions and making plans requires interpreting economic data. It may be necessary to make critical decisions on many issues that will affect our present and future. Economic literacy helps individuals and therefore institutions and society to make more rational economic decisions. In this study, it was aimed to determine the economic literacy levels of health workers. Healthcare workers are made up of different occupational groups. For this reason, it was also investigated whether the economic literacy levels of health workers differ significantly in terms of various socio-demographic variables. The data collection tool used in the research consists of two parts. In the first part, there is a personal information form to learn the socio-demographic characteristics and personal information of the participants. In the second part, there is the economy literacy scale consisting of 34 items. Scale items are intended to understand general economics knowledge. The scale of economic literacy has 4 sub-dimensions: knowledge of economy, economic rationality, social economic reflections and individual economic planning.